Evaluasi Kebijakan Harga Dasar Gabah: Studi Kasus Panen Raya Tahun 2000 - Andik Afandi (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2000)
Government gave its support to a price policy with a gabah floor price that was expected to stimulate rice pro-duction. But, during the 'great harvest' 2000, the gabah price fell below the floor price in many paddy production centre. The result'of this research concluded that the gabah floor price is too low. Above all, the goveinment was not pick-aback and implementing the floor price policy seriously. It's prove that 'cheap food policy', the policy which consumer oriented, is continuing. If this "position" not to be changed, it is potentially provoke the paddy farmer not to produce rice more. Then, the food security can be worst at the next time. Because of the serious implication would be happen, the author recommend to push-up, as an adjust-ment, the level of gabah floor price, and then it must be guarranteed (by the government) as an urgen agenda.